Análise teórica da interação de CO, CO2 e NH3 com ZnO - Martins, João B. L; Sambrano, Julio Ricardo [UNESP]; Vasconcellos, Luis Antonio da Silva [UNESP]; Longo, Elson [UNESP]; Taft, Carlton A. (Sociedade Brasileira de Química, 2004)
This paper presents a study of the interaction of small molecules with ZnO surfaces by means of theoretical methods. The AM1 semi-empirical method was used for optimizing the geometric parameters of adsorbed molecules. The optimized AM1 structures were used in the calculations of the ab initio RHF method with the 3-21G* basis set. The interaction of CO, CO2 and NH3 molecules were studied with (ZnO)22 and (ZnO)60 cluster models. We have analyzed the interaction energy, SCF orbital energies, Mulliken charges and the density of states (DOS).
Theoretical analysis of the interaction of CO, CO2, and NH3 with ZnO
Keywords: zinc oxide; interaction; theoretical methods